ENHANCING EFL LEARNERS’ READING COMPREHENSION THROUGH SQ4R METHOD AT THE SECONDARY SCHOOLS - Imroatun Nafi'ah; Susilo Susilo; Desy Rusmawaty (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
This study is intended to investigate how EFL secondary students’ reading comprehension can be enhanced through the SQ4R method. The design of this study was classroom action research which involved 31 students from class IX-A of one secondary school in Samarinda, Indonesia. Two instruments were used in this study, i.e., an observation sheet and a reading test. The observation data were qualitatively analyzed using the provided checklist, while the data from reading test was quantitatively analyzed by having percentage analysis and categorizing the results into score levels. The results revealed that the implementation of the SQ4R method could enhance the students’ reading comprehension achievement. Quantitatively, 18 students (58%) out of 31 passed the KKM (minimum completeness criteria) in cycle 1; meanwhile, in cycle 2, 27 students (87%) out of 31 students passed the KKM. In addition, problems faced by the collaborator-teacher can be solved by the dynamics happening in the two cycles, which results in the betterment of the teaching and learning process using the SQ4R method. The reflection from the two cycles showed that SQ4R can improve EFL students' reading comprehension. As the method's impacts develop, teaching and learning quality changes.